Fast Training Right on the National Examination question for Junior High School - Elin, Lailin Hijriani; Simarmata, Justin Eduardo; Siahaan, Meiva Marthaulina Lestari; Mone, Ferdinandus; Seso Delvion, Eduardus Beo; Wua Laja, Yosepha Patricia; Napitupulu, Merlin Helentina; Astriani Dewi, Ni Putu Yuni (Talenta Publisher, 2019)
Community service activity aimed to provide an understanding of mathematical concepts consists of tips and tricks to solve exam questions for junior high school students. Furthermore, the background of the implementation of this training is to get students used to solve non-routine problems found during national examination, particularly in mathematics subject. This community service was carried out from October to November 2019 with 15 participants. This activity consists of three stages starting with the field assessment, the implementation stage and the last is final stage. In the field assessment stage, the servant determines the trainees to work national examination questions quickly and accurately that is specifically for junior high school students and determine where training will be held. The second stage is the implementation stage for exposuring to rapid strategies in administering national examination, question and answer, and national examination simulation. The final stage is the evaluation stage that is an implementation evaluation of theactivities that have been arranged based on each task that has been given .Based on the training activity that have been carried out it can be concluded that the training activity adds the knowledge and skills of students in working mathematics national examination questions. In addition, this training motivates students to be more active in learning mathematics and to be more mature in preparing for the upcoming national examination. Keyword: training, national examination questions, junior high school students.